a method for manufacturing ceria nanoparticle for semiconductor CMP process using solid-state method

KR103036977B1Active Publication Date: 2026-10-21HANNAM UNIV INST FOR IND ACAD COOPERATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020240140819
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2026-10-21
Estimated Expiration
2044-10-16

Smart Images

  • Figure 112024112151517-PAT00003_ABST
    Figure 112024112151517-PAT00003_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing ceria nanoparticles, and more specifically, to a method for manufacturing ceria nanoparticles comprising: (a) a step of preparing a ceria precursor; (b) a step of heat-treating the ceria precursor to produce rod-shaped ceria nanoparticles; and (c) a step of grinding the ceria nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing ceria nanoparticles, and more specifically, to a method for manufacturing ceria nanoparticles comprising: (a) a step of preparing a ceria precursor; (b) a step of heat-treating the ceria precursor to produce rod-shaped ceria nanoparticles; and (c) a step of grinding the ceria nanoparticles. Background Technology

[0003] As semiconductor devices become more highly integrated and perform better, wiring pattern linewidths are becoming finer and structures are becoming increasingly multilayered; therefore, interlayer flatness in each process is crucial for improving photolithography precision.

[0004] The chemical-mechanical polishing (CMP) process is currently the most prominent planarization technology, and it is classified into oxide CMP, metal CMP, and poly-silicon (poly-Si) CMP processes depending on the material to be polished.

[0005] Initially, CMP slurry compositions containing silica particles were mainly used to polish oxide films, but as design rules became smaller and devices became thinner requiring high planarization, CMP slurry compositions containing cerium oxide (ceria) particles, which have a high polishing selectivity for wafers containing heterogeneous films, are being applied.

[0006] Meanwhile, a slurry composition containing ceria particles has a higher polishing speed compared to a slurry composition containing silica particles, but scratches may occur on the surface to be polished.

[0007] Therefore, there is a need for technological development of a polishing slurry composition containing ceria nanoparticles that has excellent thermal stability, dispersion stability, stability over time, polishing speed, polishing efficiency, and selective polishing characteristics, and can minimize scratches on the surface to be polished. Prior art literature

[0009] Korean Published Patent No. 10-2013-0078791 Korean Published Patent No. 10-2024-0138745 The problem to be solved

[0010] The present invention aims to solve the problems of the prior art and provides a method for manufacturing ceria nanoparticles for a polishing slurry composition that has excellent thermal stability, dispersion stability, stability over time, polishing speed, polishing efficiency, and selective polishing characteristics, and can minimize scratches on the surface to be polished. means of solving the problem

[0012] To achieve the above objectives, the present invention comprises the step of (a) preparing a ceria precursor;

[0013] (b) a step of heat-treating the ceria precursor to produce rod-shaped ceria nanoparticles; and

[0014] (c) a step of grinding the ceria nanoparticles; a method for manufacturing ceria nanoparticles is provided.

[0015] In one embodiment of the present invention, step (a) is characterized by crushing and stirring the ceria precursor.

[0016] In one embodiment of the present invention, the ceria precursor is characterized by using one or more selected from cerium carbonate, cerium sulfate, cerium acetate, cerium nitrate, and cerium chloride.

[0017] In one embodiment of the present invention, step (b) is characterized by heat-treating the ceria precursor at 400 to 800°C for 1 to 20 hours.

[0018] In one embodiment of the present invention, step (c) is characterized by grinding the ceria nanoparticles into one or more selected from a ball mill, a rod mill, a pebble mill, a burst mill, and a grinder.

[0019] In addition, the present invention provides ceria nanoparticles produced by the above-described manufacturing method. Effects of the invention

[0021] The present invention can provide a method for manufacturing ceria nanoparticles for a polishing slurry composition that has excellent thermal stability, dispersion stability, stability over time, polishing speed, polishing efficiency, and selective polishing characteristics, and can minimize scratches on the surface to be polished. Brief explanation of the drawing

[0023] Figure 1 shows the TGA and DTA results of cerium carbonate of the present invention. Figure 2 shows an SEM image of the ceria nanoparticles of the present invention. Figure 3 shows a TEM image of the ceria nanoparticles of the present invention. Figure 4 shows the DLS and zeta potential of a slurry composition containing ceria nanoparticles of the present invention. Figure 5 shows the XRD results of the ceria nanoparticles of the present invention. Specific details for implementing the invention

[0024] The present invention will be described in detail below based on the following examples. The terms and examples used in this invention are merely illustrative to explain the invention more specifically and to aid the understanding of those skilled in the art, and the scope of the rights of the present invention should not be interpreted as being limited thereto.

[0025] Unless otherwise defined, technical and scientific terms used in this invention represent the meanings commonly understood by those skilled in the art to which this invention pertains.

[0027] The present invention comprises the step of (a) preparing a ceria precursor;

[0028] (b) a step of heat-treating the ceria precursor to produce rod-shaped ceria nanoparticles; and

[0029] (c) a step of grinding the ceria nanoparticles; the present invention relates to a method for manufacturing ceria nanoparticles comprising the above steps.

[0031] Step (a) above is a step of preparing a ceria precursor, and ceria precursor particles of uniform size can be produced by grinding and mixing the ceria precursor.

[0032] Ceria precursors are converted into ceria nanoparticles through a reaction via a calcination process involving heat treatment; however, if the ceria precursor particles aggregate, the reaction with oxygen during the calcination process may not occur throughout the entire ceria precursor but only in a part of it.

[0033] In such cases, the size, distribution, shape, density, and crystallinity of the manufactured ceria particles are non-uniform, which may lead to a decrease in dispersibility, polishing speed, and polishing efficiency.

[0034] The present invention uses ceria precursor particles of uniform size by grinding and mixing a ceria precursor, thereby minimizing aggregation of the ceria precursor particles and ensuring that the reaction with oxygen during the calcination process occurs uniformly throughout the ceria precursor. Consequently, the size, distribution, shape, density, and crystallinity of the ceria particles produced are uniform, which can improve dispersibility, polishing speed, and polishing efficiency.

[0035] The above ceria precursor may be one or more selected from cerium carbonate, cerium sulfate, cerium acetate, cerium nitrate, and cerium chloride.

[0036] The present invention may use a mixture of cerium carbonate and cerium acetate as a ceria precursor.

[0037] At this time, the weight ratio of the cerium carbonate and cerium acetate is preferably 60 to 80:20 to 40, and when the weight ratio satisfies the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0038] In addition, the present invention may use a mixture of cerium carbonate, cerium acetate, and cerium nitrate as a ceria precursor.

[0039] At this time, the weight ratio of the above cerium carbonate, cerium acetate, and cerium nitrate is preferably 100:20 to 40:5 to 20, and when the weight ratio satisfies the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0041] Step (b) above can produce rod-shaped ceria nanoparticles by heat-treating the ceria precursor.

[0042] In the present invention, it is preferable to heat-treat a ceria precursor in an air or oxygen atmosphere at 400 to 800°C for 1 to 20 hours, and when the heat treatment conditions satisfy the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0043] In addition, the above step (b) is a primary heat treatment step for producing a primary product by heating the ceria precursor;

[0044] A secondary heat treatment step of heating the primary product to produce a secondary product;

[0045] A third heat treatment step of heating the above secondary product to produce a tertiary product; and

[0046] It may include a fourth heat treatment step of heating the above third product to produce a fourth product.

[0047] By performing the above heat treatment step in multiple stages, the size, distribution, shape, density, and crystallinity of the manufactured ceria particles are uniform, thereby improving dispersibility, polishing speed, and polishing efficiency.

[0049] The above first heat treatment step can produce a first product by heat treating at 400 to 500°C for 1 to 5 hours.

[0050] When the heat treatment conditions satisfy the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0052] The above second heat treatment step can produce a second product by heat treating at 510 to 600°C for 1 to 5 hours.

[0053] When the heat treatment conditions satisfy the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0055] The above third heat treatment step can produce a third product by heat treating at 610 to 700°C for 1 to 5 hours.

[0056] When the heat treatment conditions satisfy the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0058] The above fourth heat treatment step can produce a fourth product by heat treating at 710 to 800°C for 1 to 5 hours.

[0059] When the heat treatment conditions satisfy the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0061] Step (c) above is a step of grinding the ceria nanoparticles, and the ceria nanoparticles can be ground using one or more selected from a ball mill, rod mill, pebble mill, burst mill, and grinder.

[0062] It is preferable that the size (diameter) of the above-mentioned crushed ceria nanoparticles is 10 to 200 nm and the length is 50 to 700 nm.

[0064] In addition, the present invention relates to ceria nanoparticles produced by the above-described manufacturing method.

[0065] The above ceria nanoparticles have excellent thermal stability, dispersion stability, stability over time, polishing speed, polishing efficiency, and selective polishing characteristics, and can minimize scratches on the surface to be polished, so they can be used for polishing slurry compositions.

[0067] In addition, the above ceria nanoparticles can be surface-treated with a copolymer of an acrylate group-containing silane coupling agent, 2-hydroxyethyl acrylate (HEA), 2-hydroxyethyl methacrylate (HEMA), and glycidyl methacrylate.

[0068] By using the above-mentioned surface-treated ceria nanoparticles, dispersibility, polishing speed, and polishing efficiency can be improved.

[0069] The above acrylate group-containing silane coupling agents include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, methacryloxymethyltriethoxysilane, and methacryloxymethyltrimethoxysilane.

[0070] It is preferable that the weight ratio of the above acrylate group-containing silane coupling agent, 2-hydroxyethyl acrylate (HEA), 2-hydroxyethyl methacrylate (HEMA), and glycidyl methacrylate is 2~10:100:20~50:10~30.

[0071] The content of the copolymer is preferably 1 to 10 parts by weight per 100 parts by weight of ceria nanoparticles, and when the content satisfies the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0073] In addition, the ceria nanoparticles can be surface-treated with an acrylic mixture comprising methyl methacrylate, acrylic acid, and 2-hydroxyethyl acrylate (HEA).

[0074] By using the above-mentioned surface-treated ceria nanoparticles, dispersibility, polishing speed, and polishing efficiency can be improved.

[0075] The weight ratio of the above methyl methacrylate, acrylic acid, and 2-hydroxyethyl acrylate (HEA) is preferably 100:20 to 50:10 to 30.

[0076] The content of the above acrylic mixture is preferably 1 to 10 parts by weight per 100 parts by weight of ceria nanoparticles, and when the content satisfies the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0078] In addition, the above ceria nanoparticles can be surface-treated with a silane compound.

[0079] The above silane compounds may include alkoxysilanes such as tetramethoxysilane (TMOS) and tetraethoxysilane (TEOS), sodium silicate, potassium silicate, silicon tetrachloride, etc., without limitation.

[0080] The content of the above silane compound is preferably 1 to 10 parts by weight per 100 parts by weight of ceria nanoparticles, and when the content satisfies the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0081] The present invention may use a mixture of tetramethoxysilane and tetraethoxysilane as silane compounds.

[0082] At this time, the weight ratio of the tetramethoxysilane and tetraethoxysilane is preferably 60 to 80:20 to 40, and when the weight ratio satisfies the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0084] In addition, the ceria nanoparticles can be surface-treated with a composition prepared by mixing the acrylic mixture and the silane compound.

[0085] At this time, the weight ratio of the acrylic mixture and the silane compound is preferably 60 to 80:20 to 40, and when the weight ratio satisfies the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0086] The content of the above composition is preferably 1 to 10 parts by weight per 100 parts by weight of ceria nanoparticles, and when the content satisfies the above numerical range, dispersibility, polishing speed, and polishing efficiency can be maximized.

[0088] The present invention will be described in detail below through examples and comparative examples. The following examples are merely illustrative for the implementation of the present invention, and the scope of the present invention is not limited by the following examples.

[0090] (Example 1)

[0091] Cerium carbonate was crushed, mixed, and then dried.

[0092] Ceria nanoparticles were prepared by heat-treating the above-mentioned dried cerium carbonate at 500°C for 6 hours in an air atmosphere.

[0093] Rod-shaped ceria nanoparticles were prepared by grinding the above ceria nanoparticles with a ball mill.

[0095] Figure 1 shows the TGA and DTA results of cerium carbonate of the present invention.

[0096] The separation of carbonate from cerium carbonate proceeds in two stages. The first stage occurs at approximately 135°C, during which the moisture absorbed by the cerium carbonate evaporates. The second stage occurs at 200–280°C, which is the decarbonization process of cerium carbonate, and the separation is nearly completed at 300–400°C.

[0097] In differential thermal analysis, two exothermic peaks can be observed; the first is caused by the evaporation of moisture absorbed by cerium carbonate, and the second broad exothermic peak is a phenomenon caused by the separation of CO or CO2. Subsequently, crystallization occurs within the ceria particles, and it can be confirmed that the separation of carbonate is almost complete at 400°C.

[0099] Figure 2 shows an SEM image of the ceria nanoparticles of the present invention.

[0100] It can be confirmed that the ceria nanoparticles of the present invention have a rod-shaped, dense structure.

[0102] Figure 3 shows a TEM image of the ceria nanoparticles of the present invention.

[0103] It can be confirmed that the ceria nanoparticles of the present invention have a rod-shaped, dense structure.

[0105] Figure 4 shows the DLS and zeta potential of a slurry composition containing ceria nanoparticles of the present invention.

[0106] As a result of a milling test to evaluate the applicability of ceria nanoparticles to a slurry, the particle size of the ceria slurry composition of the present invention is 131.1 nm (D50), which can be confirmed to be about 13% smaller than that of a commercial ceria slurry composition.

[0107] In addition, the ceria slurry composition of the present invention exhibits pH, electrical conductivity, and zeta potential similar to commercial ceria slurry compositions.

[0109] Figure 5 shows the XRD results of the ceria nanoparticles of the present invention.

[0110] The ceria nanoparticles of the present invention exhibit peaks at the (111), (200), (220), (331), and (222) planes, which are the representative lattice structures of ceria, and from this, it can be confirmed that a ceria crystal structure is formed.

[0112] In addition, the present invention analyzed the surface area, pore volume, and pore size of ceria nanoparticles according to the heat treatment temperature.

[0113] The specific surface area of ​​cerium carbonate is 1.6 m² 2 / g, pore volume was 0.005cc / g, and pore size was 12.72nm.

[0114] The specific surface area of ​​ceria nanoparticles calcined at 400℃ is 117 m² 2 / g, pore volume is 0.096cc / g, pore size is 3.29nm, and the specific surface area of ​​ceria nanoparticles calcined at 500℃ is 94.5m² 2 / g, pore volume is 0.083cc / g, pore size is 3.52nm, and the specific surface area of ​​ceria nanoparticles calcined at 600℃ is 61.8m 2 / g, pore volume is 0.062cc / g, pore size is 4.06nm, and the specific surface area of ​​ceria nanoparticles calcined at 700℃ is 17.6m² 2 / g, pore volume is 0.036cc / g, pore size is 8.19nm, and the specific surface area of ​​ceria nanoparticles calcined at 800℃ is 4.1m 2 / g, pore volume was 0.021cc / g, and pore size was 20.6nm.

[0115] As H2O and CO2 are emitted during the heat treatment of cerium carbonate, the surface area increases; as the heat treatment temperature increases, the crystallinity of ceria increases and shrinkage occurs, causing the surface area to decrease again.

[0116] In addition, the pore volume increases with the heat treatment of cerium carbonate, and decreases again as the heat treatment temperature increases.

[0118] (Example 2)

[0119] Ceria nanoparticles were prepared using the same method as in Example 1, except that they were heat-treated at 300℃.

[0121] (Example 3)

[0122] Ceria nanoparticles were prepared using the same method as in Example 1, except that they were heat-treated at 900℃.

[0124] (Example 4)

[0125] Ceria nanoparticles were prepared in the same manner as in Example 1, except that a mixture of cerium carbonate and cerium acetate was used instead of cerium carbonate.

[0126] At this time, the weight ratio of the above cerium carbonate and cerium acetate was adjusted to 70:30.

[0128] (Example 5)

[0129] A primary heat treatment step of preparing a primary product by heating cerium carbonate at 450°C for 1.5 hours instead of heat treating cerium carbonate at 500°C for 6 hours;

[0130] A secondary heat treatment step of preparing a secondary product by heating the primary product at 550℃ for 1.5 hours;

[0131] A third heat treatment step of preparing a third product by heating the above second product at 650°C for 1.5 hours; and

[0132] Ceria nanoparticles were prepared in the same manner as in Example 1, except that a fourth heat treatment step was used to prepare a fourth product by heating the above third product at 750°C for 1.5 hours.

[0134] (Example 6)

[0135] An acrylic mixture was prepared by mixing methyl methacrylate, acrylic acid, and 2-hydroxyethyl acrylate (HEA).

[0136] At this time, the weight ratio of methyl methacrylate, acrylic acid, and 2-hydroxyethyl acrylate (HEA) was adjusted to 100:30:20.

[0137] The ceria nanoparticles prepared in Example 1 were surface-treated with the acrylic mixture.

[0138] At this time, the content of the acrylic mixture was adjusted to 5 parts by weight per 100 parts by weight of ceria nanoparticles.

[0140] (Comparative Example 1)

[0141] Ceria nanoparticles were prepared in the same manner as in Example 1, except that the step of grinding, mixing, and drying cerium carbonate was not used.

[0142] delete

[0143] delete

[0144] delete

[0145] delete

[0146] delete

[0147] delete

[0148] delete

[0149] delete

[0150] delete

[0151] delete

[0152] delete

[0153] delete

[0154] delete

[0155] delete

[0156] delete

[0157] delete

[0158] delete

[0159] delete

[0160] delete

[0161] delete

[0162] delete

[0163] delete

[0164] delete

[0165] delete

[0166] delete

[0167] delete

[0168] delete

[0169] delete

[0170] delete

Claims

Claim 1 A method for manufacturing ceria nanoparticles comprising: (a) a step of preparing a ceria precursor; (b) a step of heat-treating the ceria precursor to produce rod-shaped ceria nanoparticles; and (c) a step of grinding the ceria nanoparticles; wherein step (b) comprises: a first heat treatment step of producing a first product by heating the ceria precursor at 400 to 500°C for 1 to 5 hours; a second heat treatment step of producing a second product by heating the first product at 510 to 600°C for 1 to 5 hours; a third heat treatment step of producing a third product by heating the second product at 610 to 700°C for 1 to 5 hours; and a fourth heat treatment step of producing a fourth product by heating the third product at 710 to 800°C for 1 to 5 hours. Claim 2 A method for manufacturing ceria nanoparticles according to claim 1, wherein step (a) is characterized by crushing and stirring a ceria precursor. Claim 3 A method for manufacturing ceria nanoparticles according to claim 2, characterized in that the ceria precursor uses one or more selected from cerium carbonate, cerium sulfate, cerium acetate, cerium nitrate, and cerium chloride. Claim 4 delete Claim 5 A method for manufacturing ceria nanoparticles according to claim 1, wherein step (c) is characterized by grinding the ceria nanoparticles into one or more selected from a ball mill, a rod mill, a pebble mill, a burst mill, and a grinder. Claim 6 delete

Citation Information

Patent Citations

  • Method for preparing cerium-based polishing agent

    KR1020060005794A

  • Cerium carbonate powder, cerium oxide powder, methodfor preparing the same, and CMP slurry comprising thesame

    KR1020070051680A

  • Synthetic method of 100nm-scale cerium oxide from needle-like cerium carbonate

    KR1020110033393A

  • Menufacturing method of metal oxide particles for CMP slurry

    KR102155222B1

  • Method for preparing cerium oxide NANO powder

    KR1020080026999A